THE USE OF THE TERM UKHTI ON SOCIAL MEDIA PLATFORM X IN INDONESIA - Sobada, Indah Putri; Triwinarti, Wiwin (UI Scholars Hub, 2026)
This study traces the semantic transformation of the lexicon ukhti within Indonesia’s digital landscape. The term ukhti ( أُ خْ تِي ), derived from Arabic and meaning “my sister,” was initially used as a form of biological kinship address, later evolving into a fictional kinship address. However, in its current usage, the term increasingly conveys exclusivity and produces stereotypical perceptions of Muslim women. This study focuses on the use of ukhti on Indonesia's Social Media Platform X, examining how its meaning has become more specific and how this shift affects the representation of diverse Muslim female identities. Therefore, this study uses a qualitative approach, based on a literature review and a limited collocation analysis of social media posts on the X platform in Indonesia from September 2023 to June 2025. The data analysis is based on the lexical-semantic theory proposed by Abdul Chaer and the sociolinguistic identity theory articulated by Rob Drummond and Erik Schleef. The findings indicated that the use of ukhti maintains a positive kinship connotation within online Muslim communities, such as the Muslim Support Muslim Community. However, the emergence of collocations such as “ukhti nanggung” and “ukhti bau” reflects negative connotations that diverge from the term’s original meaning, including instances in which ukhti is misappropriated to disseminate adult content. These findings suggest that the meaning of ukhti on Social Media Platform X has undergone semantic change due to the platform’s dynamic nature and user interactions, resulting in complex implications for the representation of Muslim women’s identities.